2018
DOI: 10.2166/washdev.2018.038
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of rural sanitation in India and implications for public policy

Abstract: This article attempts to find the economic and non-economic factors determining sanitation coverage in a low income country like India. Based on National Sample Survey data of India, the analysis finds that income has a low impact, while non-economic factors have an equal or higher impact on access to and use of latrines. The number of household members has a negative impact on both access to and use of latrines. Access to and use of latrines depends on gender, age, and education of the household head. Both ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Economic condition has always been an important factor for sanitation facilities. In agreement with other studies (De, 2018; Dickinson & Pattanayak, 2009; Halder & Kabir, 2008), the findings of this present study showed that the households with higher economic status and good housing condition have better access to latrine use. Banerjee et al (2017) reported that affluent households with a pucca house are more likely to have toilets within dwelling units.…”
Section: Discussionsupporting
confidence: 93%
“…Economic condition has always been an important factor for sanitation facilities. In agreement with other studies (De, 2018; Dickinson & Pattanayak, 2009; Halder & Kabir, 2008), the findings of this present study showed that the households with higher economic status and good housing condition have better access to latrine use. Banerjee et al (2017) reported that affluent households with a pucca house are more likely to have toilets within dwelling units.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, lagged per capita net state domestic product and literacy rates have a significant and positive influence on IHHL coverage. Such a positive impact of household income and education level on latrine coverage and sanitation facilities is consistent with the findings of Ghosh and Cairncross (2014) and De (2018). The significance of education level in IHHL coverage has to be considered in line with the positive association between school sanitation facilities and the school enrollment ratio (Gillani 2021).…”
Section: Results From Econometric Modelssupporting
confidence: 82%
“…where x t and b t represent the independent variables acting as predictors of probability and the related co-efficients, respectively. Independent variables representing socio-cultural characteristics like religion and caste, which previous studies have reported as determinants of access to and usage of a toilet facility, did not alter our model, and therefore, it does not include these (De, 2018;Gupta et al, 2018;Tiwari & Nayak, 2017). This model had a statistically significant fit to the data, and its results are discussed in the next section.…”
Section: Methodsmentioning
confidence: 97%